Usage of Positional Therapy in Adults with Obstructive Sleep Apnea - de Vries, Grietje E. (J Clin Sleep Med, 2015)
STUDY OBJECTIVES: Many positional therapy (PT) strategies are available for treating positional obstructive sleep apnea (OSA). PT is primarily supplied to selected patients as a secondary treatment option when other therapies have failed. To our knowledge this is the largest study to date to assess effectiveness and long-term compliance of PT (both commercial waistband and self-made constructions, mimicking the tennis ball technique) as primary treatment in patients with different positional OSA severities. METHODS: PT was used by 53 patients, of which 40 patients underwent a follow-up polygraphic evaluation under treatment after a median time interval of 12 weeks. Patients were routinely contacted regarding their clinical status and treatment compliance. RESULTS: PT was successful in 27 out of 40 patients (68%). Overall AHI reduced significantly from a median (interquartile range [IQR]) AHI of 14.5 (10.7–19.6) to 5.9 (3.1–8.5), p < 0.001. The commercial waistband and self-made constructions were equally effective (median (IQR) reduction in overall AHI (Δ9.6 (5.5–11.9) and Δ6.8 (3.2–11.3) respectively), p = 0.22). Short-term compliance was good as most patients used PT more than 7 hours/night (mean 7.2 ± SD 1.4) and more than 6 days/week (mean 6.5 ± SD 1.3). However, after mean 13 ± 5 months, 26 patients (65%) reported they no longer used PT, especially patients with moderate positional OSA (89%). CONCLUSIONS: On the short-term, PT using the tennis ball technique, is an easy method to treat most patients with positional OSA, showing significant reductions in AHI. Unfortunately, long-term compliance is low and close follow-up of patients on PT with regard to their compliance is necessary. CITATION: de Vries GE, Hoekema A, Doff MH, Kerstjens HA, Meijer PM, van der Hoeven JH, Wijkstra PJ. Usage of positional therapy in adults with obstructive sleep apnea. J Clin Sleep Med 2015;11(2):131–137.